2018
DOI: 10.1186/s41155-018-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a brief mindfulness-based intervention on emotional regulation and levels of mindfulness in senior students

Abstract: Mindfulness-based interventions have been applied in diverse populations and achieved mental health benefits. This study examined the effects of a brief mindfulness program for emotional regulation and levels of mindfulness on senior students in Brazil. The intervention consisted of six weekly meetings attended by 30 participants. It is a pre-experimental research, with pre-and post-test comparative and correlation measurements. The preliminary results, which relied on parametrical and non-parametrical tests, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 36 publications
6
25
0
8
Order By: Relevance
“…25 In addition to longterm interventions, RCTs using brief mindfulness meditation, with sessions ranging between 3 daily sessions to 4 weekly sessions, showed that these brief mindfulness meditation interventions decreased perceived stress among university students. [26][27][28][29] In addition to its psychological effects, mindfulness meditation has been found to improve physiological indices of stress such as CRP and cortisol. 30,31 It is hypothesized that mindfulness meditation buffers stress reactivity, resulting in decreased cortisol responses and proinflammatory markers such as CRP.…”
Section: Dovepressmentioning
confidence: 99%
“…25 In addition to longterm interventions, RCTs using brief mindfulness meditation, with sessions ranging between 3 daily sessions to 4 weekly sessions, showed that these brief mindfulness meditation interventions decreased perceived stress among university students. [26][27][28][29] In addition to its psychological effects, mindfulness meditation has been found to improve physiological indices of stress such as CRP and cortisol. 30,31 It is hypothesized that mindfulness meditation buffers stress reactivity, resulting in decreased cortisol responses and proinflammatory markers such as CRP.…”
Section: Dovepressmentioning
confidence: 99%
“…Another hypothesis which explains the lack of association between the number of practices performed and the effects on depression, anxiety, and stress is related to the fact that meditation tends to increase self-awareness and makes individuals more aware of their behaviors, patterns of thinking, and emotions. In a similar study, Chiodelli et al (2018) found correlations between the amount of meditative practices and the mindfulness dimension "awareness" (r p = 0.422; p = 0.020), as well as with difficulties in emotion regulation (r s = − 0.478; p = 0.008). Cardaciotto, Herbert, Forman, Moitra, and Farrow (2008) indicate "present-moment awareness" as a fundamental dimension of mindfulness, which refers to individuals' monitoring of internal or external experience as they occur.…”
Section: Discussionmentioning
confidence: 70%
“…The space and time available for interventions in an academic environment need to be considered, as undergraduates are in a demanding context due to their curricular activities. Accordingly, studies with adapted and brief interventions have been shown to be as effective as interventions using the traditional duration protocol (Gu, Xu, and Zhu 2016;Chiodelli, Mello, Jesus, and Andretta 2018).Therefore, the objective of the present study was to identify possible effects of a brief MBI on depression, anxiety, and stress in senior students. Another aim was to assess the association between the amount of formal meditative practices performed by the participants and the results.…”
Section: Introductionmentioning
confidence: 98%
“…This finding is an important one, given the need to understand the mechanisms through which mindfulness-based interventions influence outcome variables. A growing body of evidence has suggested that one such mechanism is the enhancement of attention regulation skills, which are implicit in mindfulness (Andreu & García-Rubio, 2019;Canby et al, 2015;Chiodelli et al, 2018). This is one of the few studies that includes group variables such as shared flow.…”
Section: Discussionmentioning
confidence: 99%